Phytochemical and Biological Activity Studies of Tinospora crispa Stem (Dhaka University Journal of Science, 2020)
Three compounds namely, tinosporol A, 8-methoxy palmatine and callecdysterol C were isolated from the methanol extract of the stem of Tinospora crispa. Biological activities of different partitionates of the parent extract was also evaluated. Antimicrobial screening of different partitionates was carried out against sixteen different microorganisms and only n-hexane fraction exhibited significant zone of inhibition against Staphylococcus aureus (9 mm), Shigella boydii (9 mm), Shigella dysenteriae (9 mm), Candida albicans (10 mm) and Aspergillus niger (10 mm).The crude methanol extract showed the highest general toxicity with LC50 values of 57.14 μg/mL against brine shrimp lethality bioassay.The total antioxidant capacity of aqueous fraction was found to be 61.61 mg as ascorbic acid equivalentper gram of plant extract.The antioxidant activity of DCM fraction revealed the highest activity having IC50 values 54.74 μg/mL. No significant cytotoxicity was observed on both HeLa and Vero cell lines.Dhaka Univ. J. Sci. 68(2): 167-170, 2020 (July)